Zirconium hydroxide powder
Zirconium hydroxide powder with controlled macropores and disintegration methods enables easy pulverization and uniform mixing, addressing the aggregation issues of existing powders and enhancing battery and composite oxide performance.
Patent Information
- Application Number
- KR1020247008240
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-01
- Filing Date
- 2022-10-25
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-10-25
AI Technical Summary
Existing zirconium hydroxide powders are difficult to uniformly combine with other materials due to strong aggregation, requiring powerful disintegration methods like wet grinding, which results in dense structures with few pores for disintegration initiation points.
The development of zirconium hydroxide powder with macropores between 50 nm and 1000 nm, a total pore volume of 0.5 mL/g to 1.5 mL/g, and a specific surface area of 200 m²/g to 450 m²/g, allowing for easy disintegration without strong methods, achieved through controlled synthesis and disintegration using an ultrasonic homogenizer.
The powder can be easily pulverized with an 80% or more particle size reduction, facilitating uniform mixing with other materials and improving the performance of lithium-ion secondary batteries and composite oxides.
Smart Images

Figure 112024027468951-PCT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to zirconium hydroxide powder. Background Technology
[0002] Zirconium hydroxide powder is attracting attention as a material that improves the characteristics of lithium-ion secondary batteries. Specific examples of its use include composites with electrode active materials for the purpose of structural stabilization of electrode active materials, and applications as an inorganic filler in separators. In particular, regarding the structural stabilization of electrode active materials, it is known to be very effective when considering the high capacity of lithium-ion secondary batteries.
[0003] Patent Document 1 describes a surface area of at least 300 m² 2 / g, and the total pore volume is at least 0.70cm³ 3 Amorphous zirconium hydroxide is disclosed having a g / g and an average pore size between 5 nm and 15 nm (see Claim 1).
[0004] Patent Document 2 discloses zirconium oxide hydrate particles represented by the general formula ZrO2·nH2O, wherein the average pore diameter obtained by the nitrogen gas adsorption method of the particles is 1.5 nm or more and 1.75 nm or less, and n in the general formula is a number greater than 2.5, and n is a value measured after dispersing the particles in water, filtering them, and then drying them in air at 60°C for 6 hours (see Claim 1). Prior art literature
[0005] Patent Document 1: Japanese Patent No. 5149814 Patent Document 2: Japanese Published Patent No. 2009-274897 The problem to be solved
[0006] As with the applications described above, in applications where zirconium hydroxide powder is combined with other materials, it is generally considered important how uniformly the zirconium hydroxide powder and the other material can be combined.
[0007] As a result of careful consideration, the inventors concluded that it would be possible to obtain a more uniform composite if zirconium hydroxide powder that can be easily broken down could be provided.
[0008] The present invention has been made in consideration of the above-mentioned problem, and its purpose is to provide zirconium hydroxide powder that can be easily pulverized. means of solving the problem
[0009] The inventors conducted extensive research on zirconium hydroxide powder. As a result, they surprisingly discovered that zirconium hydroxide powder having the following composition could be easily pulverized, thereby completing the present invention.
[0010] That is, the zirconium hydroxide powder according to the present invention is,
[0011] In the pore diameter distribution obtained by the mercury indentation method, the pore diameter D in the range of 10 nm to 6000 nm 50 It is characterized by being 50nm or more and 1000nm or less.
[0012] Pores with a diameter of 50 nm or more and 1000 nm or less correspond to macropores in the secondary particles of zirconium hydroxide powder. And, the presence of these macropores becomes the starting point for the breakdown of bonding (necking) between secondary particles.
[0013] According to the above configuration, the pore diameter D in the range of 10 nm to 6000 nm 50 The aggregation structure is weak because it has macropores that are between 50 nm and 1000 nm in size and serve as the starting point for the breakdown of necking between secondary particles. Therefore, it is possible to easily disintegrate it without using a strong disintegration method.
[0014] Here, the amorphous zirconium hydroxide of Patent Document 1 has an average pore size between 5 nm and 15 nm, and the pores are mainly fine pores of 15 nm or less. In addition, the zirconium oxide hydrate particles of Patent Document 2 have an average pore diameter of 1.5 nm or more and 1.75 nm or less, and the pores are mainly fine pores of 1.75 nm or less. The fact that the pores formed by the aggregation structure are fine suggests that the contact area between primary particles is large, and it is difficult to say that the zirconium hydroxide disclosed in Patent Documents 1 and 2 can be easily broken down due to strong aggregation. Therefore, in order to finely pulverize these zirconium hydroxides, a more powerful breaking method, such as wet grinding, is required.
[0015] In addition, a method of obtaining zirconium hydroxide powder from a sol has been proposed as a general method in the past (see, for example, Japanese Patent Publication No. 3008517). However, when using this method, the specific gravity of the zirconium hydroxide obtained increases, resulting in a dense structure with few pores that serve as the starting point for aggregation and disintegration. Therefore, in order to finely pulverize the zirconium hydroxide, a more powerful disintegration method, such as wet grinding, is required.
[0016] As such, in the prior art, the pore diameter D in the range of 10 nm to 6000 nm 50 There is no description or suggestion regarding making it within the range of 50nm or more and 1000nm or less.
[0017] In the above composition, it is preferable that the total pore volume in the range of 10 nm to 6000 nm obtained by the mercury intrusion method is 0.5 mL / g to 1.5 mL / g.
[0018] If the total pore volume is 0.5 mL / g or more, it can be said that there are many macropores that serve as crack initiation points. Therefore, it is possible to pulverize it more easily.
[0019] In the above composition, it is preferable that the ratio of the amount of substance of H2O and Zr ([H2O] / [Zr]), excluding physically adsorbed water, is 0.2 or more and 1.0 or less.
[0020] If the above material amount ratio ([H2O] / [Zr]) is 0.2 or higher and 1.0 or lower, the bonding between primary particles is weak, and re-aggregation after disintegration treatment is unlikely to occur.
[0021] In the above composition, the apparent density is 0.05 g / cm³ 3 Above 1 g / cm³ 3 It is desirable that it be less than or equal to this.
[0022] The above apparent density is 1 g / cm³ 3 If the value is lower than this, it can be said that the zirconium hydroxide powder contains many pores. In other words, it can be said to have a greater number of macropores that serve as crack initiation points. Therefore, it is possible to pulverize it more easily.
[0023] In the above configuration, the particle size D after the following disintegration treatment 50 particle diameter D 50-after , particle size D before crushing treatment 50 particle diameter D 50-before When done as,
[0024] It is desirable that the particle size change rate expressed by the following formula (1) be 80% or more.
[0025] Equation (1): [Particle size change rate (%)] =
[0026] 100-([Particle diameter D 50-after ] / [Particle diameter D 50-before ])×100
[0027] <Resolve Processing>
[0028] 0.1g of zirconium hydroxide powder is added to 40mL of pure water, and homogenizer treatment is performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0029] <Release Conditions>
[0030] Transmission frequency: 20kHz
[0031] High frequency output: 200W
[0032] Amplitude control: 40±5%
[0033] The above disintegration treatment is performed under relatively calm conditions. According to the above composition, the particle size change rate becomes 80% or more through calm disintegration treatment. That is, particle size D after disintegration treatment 50 (Particle diameter D50-after ) is the particle size D before crushing treatment 50 (Particle diameter D 50-before Compared to ), it is more finely pulverized. Therefore, it can be said that the zirconium hydroxide powder is easy to pulverize.
[0034] In the above configuration, the particle size D 50-before It is preferable that the size be 50μm or more and 300μm or less.
[0035] In the above configuration, the particle size D 50-after It is preferable that the size be 0.05μm or more and 9μm or less.
[0036] In the above configuration, the specific surface area is 200m² 2 / g or more 450m 2 It is desirable that it be less than / g. Effects of the invention
[0037] According to the present invention, zirconium hydroxide powder that can be easily broken down can be provided. Brief explanation of the drawing
[0038] FIG. 1 is a schematic diagram illustrating a method for manufacturing zirconium hydroxide powder according to the present embodiment. Figure 2 is the pore distribution of zirconium hydroxide powder of Example 2, Example 7, and Comparative Example 2. Figure 3 shows the particle size distribution of the zirconium hydroxide powder of Example 1 before and after disintegration. Figure 4 shows the particle size distribution of the zirconium hydroxide powder of Example 5 before and after disintegration. Figure 5 shows the particle size distribution of the zirconium hydroxide powder of Comparative Example 1 before and after disintegration. Figure 6 is an SEM image of the zirconium hydroxide powder obtained in Example 1. Figure 7 is an SEM image of the zirconium hydroxide powder obtained in Example 6. Figure 8 is an SEM image of the zirconium hydroxide powder obtained in Comparative Example 1. Specific details for implementing the invention
[0039] Embodiments of the present invention will be described below. However, the present invention is not limited to these embodiments. Also, in this specification, zirconium hydroxide is a general term and includes an impurity metal compound containing 10 mass% or less of hafnium.
[0040] [Zirconium Hydroxide Powder]
[0041] The zirconium hydroxide powder according to the present embodiment has a pore diameter D in the range of 10 nm to 6000 nm in the pore diameter distribution obtained by the mercury intrusion method. 50 This is 50 nm or more and 1000 nm or less. Pore diameter D in the range of 10 nm or more and 6000 nm or less. 50 The aggregation structure is weak because it has macropores that are between 50 nm and 1000 nm in size and serve as the starting point for the breakdown of necking between secondary particles. Therefore, it is possible to easily disintegrate it without using a strong disintegration method.
[0042] The above pore diameter D 50 The diameter is preferably 75 nm or larger, and more preferably 100 nm or larger. The pore diameter D 50 The is preferably 800 nm or less, and more preferably 600 nm or less.
[0043] It is preferable that the above zirconium hydroxide powder has a total pore volume of 0.5 mL / g or more and 1.5 mL / g or less in the range of 10 nm to 6000 nm obtained by the mercury intrusion method. If the total pore volume is 0.5 mL / g or more, it can be said that there are many macropores that serve as crack initiation points. Therefore, it is possible to pulverize it more easily.
[0044] The above total pore volume is more preferably 0.6 mL / g or more, and even more preferably 0.7 mL / g or more. The above total pore volume is preferably larger, but for example, 1.4 mL / g or less, 1.3 mL / g or less, etc.
[0045] The above pore diameter D 50 and the total pore volume above refers to the value obtained by the method described in the example.
[0046] The above zirconium hydroxide powder has an apparent density of 0.05 g / cm³ 3 Above 1 g / cm³ 3 It is preferable that it be less than or equal to 1 g / cm³. 3 If the value is lower than this, it can be said that the zirconium hydroxide powder contains many pores. In other words, it can be said to have a greater number of macropores that serve as crack initiation points. Therefore, it is possible to pulverize it more easily.
[0047] The above apparent density is more preferably 0.80 g / cm³ 3 It is less than or equal to, and more preferably 0.60 g / cm³ 3 The above apparent density is preferably as low as possible, for example 0.10 g / cm³. 3 Above, 0.20g / cm² 3 The above is the case.
[0048] The above apparent density refers to the value obtained by the method described in the example.
[0049] The above zirconium hydroxide powder has a particle size D after the following crushing treatment. 50particle diameter D 50-after , particle size D before crushing treatment 50 particle diameter D 50-before When done as,
[0050] It is desirable that the particle size change rate expressed by the following formula (1) be 80% or more.
[0051] Equation (1): [Particle size change rate (%)] =
[0052] 100-([Particle diameter D 50-after ] / [Particle diameter D 50-before ])×100
[0053] <Resolve Processing>
[0054] 0.1g of zirconium hydroxide powder is added to 40mL of pure water, and homogenizer treatment is performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0055] <Release Conditions>
[0056] Transmission frequency: 20kHz
[0057] High frequency output: 200W
[0058] Amplitude control: 40±5%
[0059] The above-mentioned disintegration treatment is a disintegration treatment under relatively calm conditions. If the particle size change rate is 80% or more, the zirconium hydroxide powder is significantly fined by the calm disintegration treatment. Therefore, it can be said that the zirconium hydroxide powder is easy to finely pulverize.
[0060] The above particle size change rate is more preferably 83% or higher, and even more preferably 86% or higher. The above particle size change rate is more desirable as it increases, but is, for example, 99.5% or lower, 99% or lower, etc.
[0061] The above zirconium hydroxide powder has a particle size D before crushing treatment. 50 (Particle diameter D 50-beforeIt is preferable that the particle size D is 50 μm or more and 300 μm or less. 50-before 55 μm or more is more preferable, and 60 μm or more is even more preferable. In addition, the particle size D 50-before It is more preferable that it be 275 μm or less, and even more preferable that it be 250 μm or less.
[0062] The above zirconium hydroxide powder has a particle size D after crushing treatment. 50 (Particle diameter D 50-after It is preferable that the particle size D is 0.05 μm or more and 9 μm or less. 50-after It is more preferable that it be 0.07 μm or larger, and even more preferable that it be 0.1 μm or larger. In addition, the particle size D 50-after는 7 μm or less is more preferable, and 5 μm or less is even more preferable.
[0063] The above zirconium hydroxide powder has a particle size D before crushing treatment. 10 (Particle diameter D 10-before It is preferable that the particle size D is 0.5 μm or more and 50 μm or less. 10-before 1 μm or more is more preferable, and 2 μm or more is even more preferable. In addition, the particle size D 10-before It is more preferable that it be 40 μm or less, and even more preferable that it be 30 μm or less.
[0064] The above zirconium hydroxide powder has a particle size D after the following crushing treatment. 10 (Particle diameter D 10-after It is preferable that ) is 0.1 μm or more and 2.5 μm or less. The particle size D 10-after 0.2 μm or more is more preferable, and 0.3 μm or more is even more preferable. In addition, the particle size D 10-after It is more preferable that it be 2.0 μm or less, and even more preferable that it be 1.5 μm or less.
[0065] The above particle size D 10-afterIf the particle size is 2.5 μm or less, it can be said that it has been significantly micronized by the following pulverization treatment. Therefore, it can be said that the zirconium hydroxide powder is easy to micronize.
[0066] <Resolve Processing>
[0067] 0.1g of zirconium hydroxide powder is added to 40mL of pure water, and homogenizer treatment is performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0068] <Release Conditions>
[0069] Transmission frequency: 20kHz
[0070] High frequency output: 200W
[0071] Amplitude control: 40±5%
[0072] The above zirconium hydroxide powder has a particle size D before crushing treatment. 90 (Particle diameter D 90-before It is preferable that the particle size D is 200 μm or more and 900 μm or less. 90-before 250 μm or more is more preferable, and 300 μm or more is even more preferable. In addition, the particle size D 90-before It is more preferable that it be 850 μm or less, and even more preferable that it be 800 μm or less.
[0073] The above zirconium hydroxide powder has a particle size D after the following crushing treatment. 90 (Particle diameter D 90-after It is preferable that the particle size D is 1 μm or more and 10 μm or less. 90-after 2 μm or more is more preferable, and 3 μm or more is even more preferable. In addition, the particle size D 90-after It is more preferable that it be 9 μm or less, and even more preferable that it be 8 μm or less.
[0074] The above particle size D 90-afterIf the particle size is 10 μm or less, it can be said that no coarse particles remain after the following crushing treatment. Therefore, it can be said that the zirconium hydroxide powder is easy to pulverize.
[0075] <Resolve Processing>
[0076] 0.1g of zirconium hydroxide powder is added to 40mL of pure water, and homogenizer treatment is performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0077] <Release Conditions>
[0078] Transmission frequency: 20kHz
[0079] High frequency output: 200W
[0080] Amplitude control: 40±5%
[0081] It is preferable that the mode diameter of the above zirconium hydroxide powder before crushing treatment is 50 μm or more and 700 μm or less. It is more preferable that the mode diameter before crushing treatment is 70 μm or more, and even more preferable that it is 90 μm or more. In addition, it is more preferable that the mode diameter before crushing treatment is 650 μm or less, and even more preferable that it is 600 μm or less.
[0082] It is preferable that the above zirconium hydroxide powder has a mode diameter of 0.5 μm or more and 6 μm or less after the following crushing treatment. It is more preferable that the mode diameter after the crushing treatment is 1 μm or more, and even more preferable that it is 2 μm or more. Furthermore, it is more preferable that the mode diameter after the crushing treatment is 5 μm or less, and even more preferable that it is 4 μm or less.
[0083] If the mode diameter after the above-mentioned disintegration treatment is 6 μm or less, it can be said that the powder has been significantly micronized by the following disintegration treatment. Therefore, it can be said that the zirconium hydroxide powder is easy to micronize.
[0084] <Resolve Processing>
[0085] 0.1g of zirconium hydroxide powder is added to 40mL of pure water, and homogenizer treatment is performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0086] <Release Conditions>
[0087] Transmission frequency: 20kHz
[0088] High frequency output: 200W
[0089] Amplitude control: 40±5%
[0090] It is preferable that the above zirconium hydroxide powder has an average particle size of 80 μm or more and 500 μm or less before crushing treatment. It is more preferable that the average particle size before crushing treatment is 90 μm or more, and even more preferable that it is 100 μm or more. In addition, it is more preferable that the average particle size before crushing treatment is 450 μm or less, and even more preferable that it is 400 μm or less.
[0091] It is preferable that the above zirconium hydroxide powder has an average particle size of 0.5 μm or more and 10 μm or less after the following crushing treatment. It is more preferable that the average particle size after the crushing treatment is 1 μm or more, and even more preferable that it is 2 μm or more. In addition, it is more preferable that the average particle size after the crushing treatment is 8 μm or less, and even more preferable that it is 6 μm or less.
[0092] If the average particle size after the above-mentioned disintegration treatment is 10 μm or less, it can be said that the particle size has been significantly reduced by the following disintegration treatment. Therefore, it can be said that the zirconium hydroxide powder is easy to reduce.
[0093] <Resolve Processing>
[0094] 0.1g of zirconium hydroxide powder is added to 40mL of pure water, and homogenizer treatment is performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0095] <Release Conditions>
[0096] Transmission frequency: 20kHz
[0097] High frequency output: 200W
[0098] Amplitude control: 40±5%
[0099] The above particle size D 50-before , particle size D 50-after , particle size D 10-before , particle size D 10-after , particle size D 90-before , particle size D 90-after The mode diameter before disintegration treatment, the mode diameter after disintegration treatment, the average particle size before disintegration treatment, and the average particle size after disintegration treatment refer to values obtained by the method described in the example.
[0100] The above zirconium hydroxide powder has a specific surface area of 200 m² 2 / g or more 450m 2 It is preferable that it be / g or less. The above specific surface area is more preferably 220 m² 2 / g or more, and more preferably 250m 2 It is greater than / g. While a larger specific surface area is preferable, for example, 400m 2 / g or less, 350m 2 / g is less than or equal to etc.
[0101] The above specific surface area refers to the value obtained by the method described in the example.
[0102] Zirconium hydroxide is a compound represented by the general formula ZrO(OH)2·nH2O(n>0). Additionally, zirconium hydroxide is a compound represented by the general formula ZrO2·nH2O(n>0). The zirconium hydroxide powder according to the present embodiment comprises both the powder of zirconium hydroxide and the powder of zirconium hydroxide.
[0103] The above n is preferably 2 or less, and more preferably 1.5 or less. If the above n is 2 or less, the moisture content is low and re-aggregation after crushing treatment is unlikely to occur. The number of the above n can be adjusted, for example, by the temperature or time of the drying process.
[0104] It is preferable that the above zirconium hydroxide powder be amorphous. Whether the zirconium hydroxide powder is crystalline or amorphous is determined by X-ray diffraction measurement of the powder. When the zirconium hydroxide powder is crystalline, a clear diffraction peak is observed in the range of 2θ = 28° to 31°, but when it is amorphous, the peak in that range is broad, and the crystallite diameter calculated from the full width at half maximum is 3 nm or less.
[0105] It is preferable that the above zirconium hydroxide powder has a substance ratio ([H2O] / [Zr]) of H2O and Zr excluding physically adsorbed water of 0.2 or more and 1.0 or less.
[0106] Here, physically adsorbed water refers to water that is released by heating at 195°C or lower. That is, H2O excluding physically adsorbed water refers to chemically adsorbed water (crystallized water).
[0107] If the above material amount ratio ([H2O] / [Zr]) is 0.2 or higher and 1.0 or lower, the bonding between primary particles is weak, and re-aggregation after disintegration treatment is unlikely to occur.
[0108] The above amount of substance ratio ([H2O] / [Zr]) is more preferably 0.3 or higher, and even more preferably 0.4 or higher. The above amount of substance ratio ([H2O] / [Zr]) is more preferably 0.9 or lower, and even more preferably 0.8 or lower.
[0109] The above substance amount ratio ([H2O] / [Zr]) refers to the value obtained by the method described in the example.
[0110] The uses of the above zirconium hydroxide powder are not particularly limited, but since it can be easily crushed, it can be used, for example, as a raw material powder in the synthesis of battery components such as lithium-ion secondary batteries or composite oxides containing Zr. When used as a battery component such as a lithium-ion secondary battery, it can be uniformly combined when combined with other materials, so an improvement in the performance of the component or battery can be expected. In addition, when used as a raw material powder in the synthesis of composite oxides containing Zr, it becomes possible to adjust the sample to a more uniform state when synthesizing the composite oxide by a method using a ball mill or mixer (solid-state method). That is, when the above zirconium hydroxide powder is used as a raw material powder in the synthesis of the above composite oxide, it is easily crushed into fine particles, so it becomes possible to adjust the sample to a more uniform state.
[0111] [Method for manufacturing zirconium hydroxide powder]
[0112] Hereinafter, an example of a method for manufacturing zirconium hydroxide powder is described. However, the method for manufacturing zirconium hydroxide powder according to the present invention is not limited to the following example.
[0113] The method for manufacturing zirconium hydroxide powder according to the present embodiment is
[0114] Process 1 of heating a zirconium salt solution with a Zr concentration of 0.5M or more and 2.0M or less to 60℃ or more and 90℃ or less
[0115] Process 2 of heating a sulfating agent solution to between 60°C and 90°C, and
[0116] It includes process 3, which involves contacting the zirconium salt solution after heating with the sulfate solution after heating and immediately introducing them into an alkaline solution.
[0117] The following explains each process in detail.
[0118] Process 1
[0119] In process 1, a zirconium salt solution with a Zr concentration of 0.5 M or more and 2.0 M or less is heated to a temperature of 60°C or higher and 90°C or lower.
[0120] As for the zirconium salt used to prepare the above zirconium salt solution, it is sufficient to supply zirconium ions, and examples include zirconium oxynitrate, zirconium oxychloride, and zirconium nitrate. These may be used in one or more types. Among these, zirconium oxychloride is preferred due to its high productivity on an industrial scale.
[0121] The solvent used to prepare the above zirconium salt solution may be selected according to the type of zirconium salt, etc. Typically, water (pure water, ion-exchanged water, hereinafter the same) is preferred.
[0122] As described above, the concentration of the zirconium salt solution is set to a Zr concentration of 0.5 M or higher and 2.0 M or lower. By setting the concentration of the zirconium salt solution to 0.5 M or higher and 2.0 M or lower, the rate of formation of basic zirconium sulfate particles (ZBS particles) generated when in contact with a sulfating agent solution can be slowed down, thereby appropriately inhibiting the growth of ZBS particles. From the perspective of appropriately inhibiting the growth of ZBS particles, the concentration of the zirconium salt solution is preferably a Zr concentration of 1.8 M or lower, and more preferably a Zr concentration of 1.6 M or lower. From the perspective of not excessively inhibiting the formation of ZBS particles, the concentration of the zirconium salt solution is preferably a Zr concentration of 0.7 M or higher, and more preferably a Zr concentration of 1.0 M or higher.
[0123] In addition, as described above, in Process 1, the zirconium salt solution is heated to a temperature of 60°C or higher and 90°C or lower. By setting the temperature of the zirconium salt solution to 60°C or higher and 90°C or lower, the rate of formation of basic zirconium sulfate particles (ZBS particles) generated when in contact with a sulfating agent solution can be slowed down, thereby appropriately inhibiting the growth of ZBS particles. From the perspective of appropriately inhibiting the growth of ZBS particles, the temperature of the zirconium salt solution is preferably 85°C or lower, and more preferably 80°C or lower. From the perspective of not excessively inhibiting the formation of ZBS particles, the temperature of the zirconium salt solution is preferably 65°C or higher, and more preferably 70°C or higher.
[0124] Process 2
[0125] In process 2, the sulfating agent solution is heated to a temperature of 60°C or higher and 90°C or lower. Additionally, process 2 may be performed in parallel with process 1.
[0126] As for the sulfating agent, it is sufficient to have a substance that reacts with zirconium ions to produce a sulfate (i.e., a reagent that sulfates), and examples include sulfuric acid, sodium sulfate, potassium sulfate, ammonium sulfate, potassium hydrogen sulfate, sodium hydrogen sulfate, potassium disulfate, sodium disulfate, and sulfur trioxide. The sulfating agent may be in any form, such as powder or solution, but a solution (especially an aqueous solution) is preferred. As for the solvent, the same solvent used to prepare the zirconium salt solution may be used.
[0127] It is preferable that the acid concentration of the above zirconium salt solution be 0.1 to 2.0 N. By setting the acid concentration to the above range, the aggregation state of the particles constituting the zirconium hydroxide powder can be controlled to a suitable state. The acid concentration can be adjusted by using, for example, hydrochloric acid, nitric acid, sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, etc.
[0128] The concentration of the above sulfating agent (the above sulfating agent solution) is not particularly limited, but it is preferable to have a concentration of 0.1 to 3.0 M.
[0129] As described above, in Process 2, the sulfating agent solution is heated to a temperature of 60°C or higher and 90°C or lower. By maintaining the temperature of the sulfating agent solution at 60°C or higher and 90°C or lower, the growth rate of basic zirconium sulfate particles (ZBS particles) generated when in contact with the zirconium salt solution can be appropriately suppressed. From the perspective of appropriately suppressing the growth of ZBS particles, the temperature of the sulfating agent solution is preferably 85°C or lower, and more preferably 80°C or lower. From the perspective of not excessively suppressing the formation reaction of ZBS particles, the temperature of the sulfating agent solution is preferably 65°C or higher, and more preferably 70°C or higher. In addition, it is preferable to make the temperature of the sulfating agent solution the same as the temperature of the zirconium salt solution.
[0130] The container for preparing the zirconium salt solution and the sulfating agent solution is provided to have a capacity sufficient to sufficiently stir the zirconium salt solution and the sulfating agent solution, respectively, and the material is not particularly limited. However, it is preferable to have equipment capable of appropriately heating each solution so that the temperature does not fall below 60°C. For example, it is preferable to install a heater in the piping supplying each solution (e.g., the T-pipe (20) described later).
[0131] Process 3
[0132] In process 3, the zirconium salt solution after heating and the sulfate solution after heating are brought into contact and immediately added to the alkaline solution.
[0133] Process 3 will be explained below with reference to the drawings.
[0134] FIG. 1 is a schematic diagram illustrating a method for manufacturing zirconium hydroxide powder according to the present embodiment. As shown in FIG. 1, a container (10) is connected to one end (left in FIG. 1) above a T-tube (20) via a metering pump (12). A container (30) is connected to the other end (right in FIG. 1) above a T-tube (20) via a metering pump (32). A zirconium solution heated to 60°C or higher and 90°C or lower is stored in the container (10). A sulfating agent solution heated to 60°C or higher and 90°C or lower is stored in the container (30).
[0135] Additionally, an alkaline solution is placed in the container (40) and positioned below the T-tube (20). The alkali is not limited to, for example, potassium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia, hydrazine, ammonium bicarbonate, etc. The concentration of the alkali is not particularly limited, but is typically used at 5 to 30% by diluting with water.
[0136] It is preferable that the alkaline solution be heated to a temperature of 70°C or higher and 100°C or lower. If the temperature of the alkaline solution is 70°C or higher, the formation of aggregated particles proceeds rapidly, and if the temperature of the alkaline solution is 100°C or lower, changes in the concentration of the solution due to water evaporation can be suppressed. More preferably, the temperature of the alkaline solution is 95°C or lower, and even more preferably 90°C or lower. More preferably, the temperature of the alkaline solution is 75°C or higher, and even more preferably 85°C or higher.
[0137] In addition, in this embodiment, a case is described in which a zirconium solution and a sulfate solution are brought into contact using a T-tube (20), and then the mixture is introduced into an alkaline solution placed below. However, the mechanism for bringing the zirconium solution and the sulfate solution into contact is not limited to a T-tube (20), and a glass Y-shaped tube connector, etc., may also be used.
[0138] In process 3, the zirconium solution and the sulfate solution are brought into contact by controlling the flow rate of the zirconium solution by the quantitative flow pump (12) and the flow rate of the sulfate solution by the quantitative flow pump (32). The mixture obtained by contact (basic zirconium sulfate-containing reaction solution) is introduced (introduced) directly into the alkaline solution in the container (40) from below the T-tube (20).
[0139] By immediately introducing (dropping) the mixture (reaction solution containing basic zirconium sulfate) obtained by contacting the zirconium solution with the sulfating agent solution into the alkaline solution, the formed basic zirconium sulfate particles (ZBS particles) are instantaneously neutralized and electrically aggregated, thereby the pore diameter D 50 Zirconium hydroxide powder within the range of 50 nm to 1000 nm can be obtained.
[0140] In addition, "introducing the mixed solution directly into the alkaline solution" means that the mixed solution is rapidly introduced into the alkaline solution by setting the delivery speed of the zirconium solution by the quantitative delivery pump (12) and the delivery speed of the sulfating agent solution by the quantitative delivery pump (32) within an appropriate range.
[0141] Specifically, “introducing the mixed solution directly into the alkaline solution” means that the zirconium solution’s transfer rate by the quantitative transfer pump (12) is set to a range of 1 mL / min or more and 25 mL / min or less, and the sulfating agent solution’s transfer rate by the quantitative transfer pump (32) is set to a range of 0.2 mL / min or more and 5 mL / min or less, so that the mixed solution (mixed portion) obtained by contacting the zirconium salt solution and the sulfating agent solution after heating is introduced directly into the alkaline solution.
[0142] The delivery rate of the zirconium solution is more preferably 5 mL / min or more, and even more preferably 10 mL / min or more. The delivery rate of the zirconium solution is more preferably 20 mL / min or less, and even more preferably 15 mL / min or less.
[0143] The delivery rate of the above sulfating agent solution is more preferably 1 mL / min or more, and even more preferably 2 mL / min or more. The delivery rate of the above sulfating agent solution is more preferably 4 mL / min or less, and even more preferably 3 mL / min or less.
[0144] The diameter of the tube (L1) (see FIG. 1) for delivering the zirconium solution is preferably 1 mm or more and 10 mm or less. More preferably, the tube diameter (L1) is 2 mm or more, and even more preferably 4 mm or more. More preferably, the tube diameter (L1) is 8 mm or less, and even more preferably 6 mm or less.
[0145] The diameter of the tube (L2) (see FIG. 1) for delivering the sulfating agent solution is preferably 1 mm or more and 10 mm or less. More preferably, the tube diameter (L2) is 2 mm or more, and even more preferably 4 mm or more. More preferably, the tube diameter (L2) is 8 mm or less, and even more preferably 6 mm or less.
[0146] If the flow rate of the zirconium solution by the quantitative flow pump (12), the flow rate of the sulfating agent solution by the quantitative flow pump (32), the tube diameter (L1), and the tube diameter (L2) are within the above ranges, it becomes easier to immediately introduce the mixed solution into the alkaline solution.
[0147] The alkaline solution is not particularly limited as long as it can produce a hydroxide, but it is preferable that the pH be adjusted to be 9 or higher, preferably 12.5 or higher, even after the entire mixture has been added dropwise.
[0148] In addition, after adding the above mixture dropwise to the above alkaline solution, additional alkaline solution may be added.
[0149] Afterward, it is advisable to remove impurities by rinsing with pure water or the like as needed. After rinsing, drying or the like can be performed as necessary.
[0150] The above describes the method for manufacturing zirconium hydroxide powder according to the present embodiment.
[0151] Example
[0152] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples as long as it does not exceed the gist thereof. In addition, the zirconium hydroxide powder obtained in the examples and comparative examples contains 1 to 3 mass% of hafnium relative to zirconium as an unavoidable impurity (calculated by the following formula (X)).
[0153] <Food(X)>
[0154] ([Mass of Hafnium] / ([Mass of Zirconium] + [Mass of Hafnium])) × 100 (%)
[0155] The maximum and minimum values of the content of each component shown in the following examples should be considered as the preferred minimum and maximum values of the present invention, regardless of the content of other components.
[0156] In addition, the maximum and minimum values of the measurements shown in the following examples should be considered as the preferred minimum and maximum values of the present invention, regardless of the content (composition) of each component.
[0157] [Production of Zirconium Hydroxide Powder]
[0158] (Example 1)
[0159] 100 mL of an aqueous solution of zirconium oxychloride (Zr concentration = 1.6 M) and 35 mL of an aqueous solution of sodium sulfate (Na2SO4 concentration = 1.6 M) were each heated to 70°C, and 250 mL of an aqueous solution of sodium hydroxide (NaOH concentration = 0.5 mM) was heated to 90°C. Afterward, the two solutions of the aqueous solution of zirconium oxychloride and the aqueous solution of sodium sulfate were mixed by transferring the liquid using a quantitative transfer pump, and then the mixed solution was transferred as is into the aqueous solution of sodium hydroxide heated to 90°C.
[0160] At this time, a tigon tube with an inner diameter of 4 mm was used, and a glass Y-shaped tube connector was used at the junction of the two solutions to perform the two-solution mixing reaction. In addition, the delivery rate of the aqueous zirconium oxychloride solution was set to 10 mL / min, and the flow rate of the aqueous sodium sulfate solution was set to 3.5 mL / min.
[0161] A mixture of each aqueous solution was stirred as is at 90°C for 30 minutes, and then a sodium hydroxide aqueous solution (NaOH concentration = 0.1 M) was added until the pH became 11 or higher to obtain a slurry containing zirconium hydroxide. Next, after filtration, a cake made of zirconium hydroxide was obtained by washing with distilled water until the amount of Na and Cl contained in the precipitate was less than 100 ppm.
[0162] Zirconium hydroxide powder according to Example 1 was obtained by heat-treating the recovered zirconium hydroxide cake at 200°C for 1 hour using a dryer.
[0163] The obtained zirconium hydroxide powder was amorphous. It was confirmed that the obtained zirconium hydroxide powder was amorphous by powder X-ray diffraction measurement. In addition, for the following Examples 2 to 10 and Comparative Examples 1 to 5, it was also confirmed by powder X-ray diffraction measurement that the obtained zirconium hydroxide powder was amorphous.
[0164] (Example 2)
[0165] Zirconium hydroxide powder according to Example 2 was obtained in the same manner as Example 1, except that the drying time was changed to 2 hours.
[0166] (Example 3)
[0167] Zirconium hydroxide powder according to Example 3 was obtained in the same manner as Example 1, except that the drying time was changed to 3 hours.
[0168] (Example 4)
[0169] Zirconium hydroxide powder according to Example 4 was obtained in the same manner as Example 1, except that the drying time was changed to 24 hours.
[0170] (Example 5)
[0171] Zirconium hydroxide powder according to Example 5 was obtained in the same manner as Example 1, except that the drying time was changed to 96 hours.
[0172] (Example 6)
[0173] Zirconium hydroxide powder according to Example 6 was obtained in the same manner as in Example 1, except that the concentration of the sodium sulfate aqueous solution was 2.2 M.
[0174] (Example 7)
[0175] Zirconium hydroxide powder according to Example 7 was obtained in the same manner as Example 6, except that the drying time was changed to 2 hours.
[0176] (Example 8)
[0177] Zirconium hydroxide powder according to Example 8 was obtained in the same manner as Example 6, except that the drying time was changed to 3 hours.
[0178] (Example 9)
[0179] Zirconium hydroxide powder according to Example 9 was obtained in the same manner as in Example 6, except that the drying time was changed to 24 hours.
[0180] (Example 10)
[0181] Zirconium hydroxide powder according to Example 10 was obtained in the same manner as in Example 6, except that the drying time was changed to 96 hours.
[0182] (Comparative Example 1)
[0183] A slurry containing zirconium hydroxide was obtained by adding ammonia water to 100 mL of an aqueous zirconium oxychloride solution (Zr=1.0M) until the pH reached 8. Next, the slurry was filtration, and a cake made of zirconium hydroxide was obtained by washing with distilled water until the amount of Na and Cl contained in the precipitate was less than 100 ppm. 500 mL of distilled water was added to the obtained cake, and aging was performed at 90°C for 8 hours. After the aging was completed, the slurry was filtration, and the obtained cake was heat-treated at 200°C for 1 hour using a dryer to obtain the zirconium hydroxide powder according to Comparative Example 1.
[0184] (Comparative Example 2)
[0185] Zirconium hydroxide powder according to Comparative Example 2 was obtained in the same manner as Comparative Example 1, except that the drying time was changed to 2 hours.
[0186] (Comparative Example 3)
[0187] Zirconium hydroxide powder according to Comparative Example 3 was obtained in the same manner as Comparative Example 1, except that the drying time was changed to 3 hours.
[0188] (Comparative Example 4)
[0189] Zirconium hydroxide powder according to Comparative Example 4 was obtained in the same manner as Comparative Example 1, except that the drying time was changed to 24 hours.
[0190] (Comparative Example 5)
[0191] Zirconium hydroxide powder according to Comparative Example 5 was obtained in the same manner as Comparative Example 1, except that the drying time was changed to 96 hours.
[0192] [Determination of water content at 195℃ and mass ratio after 195℃ ([H2O] / [Zr]]]
[0193] Using the Rigakusa product, Thermo Plus TG8120, the following<TG-DTA 측정 조건> The water content was determined from the weight loss rate from the start of heating up to 195°C. In addition, the ZrO2 content was quantified from the weight loss rate from the start of heating up to 1000°C.
[0194] <TG-DTA 측정 조건>
[0195] Sample weight: 20 mg
[0196] Sample container: Platinum pan (φ5.2mm, H5mm)
[0197] Heating rate: 10℃ / min
[0198] Temperature range: 30℃ ~ 1000℃
[0199] Standard sample: Al2O3 powder 20 mg
[0200] Next, using the obtained water content and ZrO2 content, the mass ratio ([H2O] / [Zr]) after heating to 195°C was obtained by the following formula. Also, in the formula, 18 is the molecular weight of water and 123.22 is the molecular weight of ZrO2. The results are shown in Table 1.
[0201] [H2O] / [Zr]=([H2O content] / 18) / ([ZrO2 content] / 123.22)
[0202] [Measurement of Crafting Volume]
[0203] The pore distribution of the zirconium hydroxide powders of the Examples and Comparative Examples was obtained by the mercury intrusion method using a pore distribution measuring device ("Autopore IV9500," Micromerics product). The measurement conditions are as follows.
[0204] <Measurement Conditions>
[0205] Measuring device: Pore distribution measuring device (Micromerics product Autopore IV9500)
[0206] Measurement range: 0.0036 ~ 10.3μm
[0207] Measurement Score: 120 points
[0208] Mercury contact angle: 140 degrees
[0209] Mercury surface tension: 480 dyne / cm
[0210] Using the obtained pore distribution, pore diameter D in the range of 10 nm to 6000 nm 50 and the total pore volume in the range of 10 nm to 6000 nm was calculated. The results are shown in Table 1.
[0211] In addition, Figure 2 shows the pore distribution of the zirconium hydroxide powders of Example 2, Example 7, and Comparative Example 2. These are all zirconium hydroxide powders that were dried for 2 hours during preparation.
[0212] [Measurement of Apparent Density]
[0213] For the zirconium hydroxide powders of the examples and comparative examples, the apparent density of the zirconium hydroxide powder was determined from the weight of the zirconium hydroxide powder filled into a volume of 30 ml in accordance with JIS K 5101. The results are shown in Table 1.
[0214] [Measurement of Specific Surface Area]
[0215] The specific surface area of the zirconium hydroxide powders of the examples and comparative examples was measured by the BET method using a specific surface area meter ("Maxov" Mountech product). The results are shown in Table 1.
[0216] [Particle size D before crushing treatment 50 (Particle diameter D 50-before ), particle size D before crushing treatment 10 (Particle diameter D 10-before ), particle size D before crushing treatment 90 (Particle diameter D 90-before ), measurement of mode diameter before crushing treatment, and average particle size before crushing treatment]
[0217] 0.15 g of zirconium hydroxide powder from the examples and comparative examples and 40 ml of 0.2% sodium hexametaphosphate aqueous solution were placed in a 50 ml beaker and dispersed for 5 minutes using a benchtop ultrasonic cleaner “W-113” (manufactured by Honda Electronics Co., Ltd.), then placed into a device (laser diffraction particle size distribution measuring device (“SALD-2300” manufactured by Shimadzu Corporation)) for measurement. The results are shown in Table 2.
[0218] [Particle size D after disintegration treatment 50 (Particle diameter D 50-after ), particle size D after disintegration treatment 10 (Particle diameter D 10-after ), particle size D after disintegration treatment 90 (Particle diameter D 90-after ), measurement of mode diameter after disintegration treatment, and average particle size after disintegration treatment]
[0219] The zirconium hydroxide powder of the examples and comparative examples was pulverized according to the following pulverization treatment.
[0220] <Resolve Processing>
[0221] 0.1g of zirconium hydroxide powder was added to 40mL of pure water, and homogenizer treatment was performed for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: product name Digital Sonifier 250.
[0222] <Release Conditions>
[0223] Transmission frequency: 20kHz
[0224] High frequency output: 200W
[0225] Amplitude control: 40±5%
[0226] 0.15 g of zirconium hydroxide powder after the above-mentioned disintegration treatment and 40 ml of 0.2% sodium hexametaphosphate aqueous solution were placed in a 50 ml beaker and dispersed for 5 minutes using a benchtop ultrasonic cleaner “W-113” (manufactured by Honda Electronics Co., Ltd.), then placed into a device (laser diffraction particle size distribution measuring device (“SALD-2300” manufactured by Shimadzu Corporation)) for measurement. The results are shown in Table 2.
[0227] In addition, Table 2 shows the particle size change rate indicated by the following formula (1).
[0228] Equation (1): [Particle size change rate (%)] =
[0229] 100-([Particle diameter D 50-after ] / [Particle diameter D 50-before ])×100
[0230] Figure 3 shows the particle size distribution of the zirconium hydroxide powder of Example 1 before and after disintegration. Figure 4 shows the particle size distribution of the zirconium hydroxide powder of Example 5 before and after disintegration. Figure 5 shows the particle size distribution of the zirconium hydroxide powder of Comparative Example 1 before and after disintegration. In Figures 3, 4, and 5, the dotted line represents the particle size distribution before disintegration, and the solid line represents the particle size distribution after disintegration.
[0231] As can be seen from FIGS. 3 to 5, the particle size distribution of the zirconium hydroxide powder according to Example 1 and Example 5 after disintegration is generally shifted significantly to the left (low particle size side), and it can be seen that the micronization by disintegration treatment is significant compared to the zirconium hydroxide powder according to Comparative Example 1.
[0232] [SEM Observation]
[0233] Figure 6 shows an SEM image of the zirconium hydroxide powder obtained in Example 1, Figure 7 shows an SEM image of the zirconium hydroxide powder obtained in Example 6, and Figure 8 shows an SEM image of the zirconium hydroxide powder obtained in Comparative Example 1.
[0234] As shown in FIGS. 6 and 7, voids of the order of several μm could be observed in the zirconium hydroxide powder of Example 1 and Example 6. On the other hand, as shown in FIG. 8, voids of the order of several μm were not observed in the zirconium hydroxide powder of the Comparative Example.
[0235] Also, although not shown, the zirconium hydroxide powders of Examples 2 to 5 could obtain the same SEM image as the zirconium hydroxide powder of Example 1. Also, although not shown, the zirconium hydroxide powders of Examples 7 to 10 could obtain the same SEM image as the zirconium hydroxide powder of Example 6.
[0236] From these results as well, it became evident that the zirconium hydroxide powder of the examples has an aggregation structure containing many macropores that contribute to crack formation between particles.
[0237]
[0238]
Claims
Claim 1 In the pore diameter distribution obtained by the mercury indentation method, the pore diameter D in the range of 10 nm to 6000 nm 50 Zirconium hydroxide powder characterized by having a diameter of 50 nm or more and 1000 nm or less, and a total pore volume of 0.5 mL / g or more and 1.5 mL / g or less in the range of 10 nm or more and 6000 nm or less obtained by the mercury intrusion method. Claim 2 Zirconium hydroxide powder according to claim 1, characterized in that the total pore volume in the range of 10 nm to 6000 nm obtained by the mercury intrusion method is 0.7 mL / g to 1.3 mL / g. Claim 3 Zirconium hydroxide powder according to claim 1 or claim 2, characterized in that the ratio of the amount of substance of H2O and Zr ([H2O] / [Zr]), excluding physically adsorbed water, is 0.2 or more and 1.0 or less. Claim 4 In claim 1 or claim 2, the apparent density is 0.05 g / cm³ 3 Above 1 g / cm³ 3 Zirconium hydroxide powder characterized by the following: Claim 5 In claim 1 or claim 2, the particle size D after the following disintegration treatment 50 particle diameter D 50-after , particle size D before crushing treatment 50 particle diameter D 50-before Zirconium hydroxide powder characterized by having a particle size change rate expressed by the following formula (1) of 80% or more when [calculated as follows]. Formula (1): [Particle size change rate (%)] = 100 - ([Particle size D 50-after ] / [Particle diameter D 50-before ])×100 <Disintegration Treatment> Add 0.1g of zirconium hydroxide powder to 40mL of pure water, and perform homogenizer treatment for 5 minutes under the following disintegration conditions using a BRANSON ultrasonic homogenizer: Product name Digital Sonifier 250. <Disintegration Conditions> Transmission frequency: 20kHz High frequency output: 200W Amplitude control: 40±5% Claim 6 In claim 5, the particle size D 50-before Zirconium hydroxide powder characterized by having a particle size of 50 μm or more and 300 μm or less. Claim 7 In claim 5, the particle size D 50-after Zirconium hydroxide powder characterized by having a particle size of 0.05 μm or more and 9 μm or less. Claim 8 In claim 1 or claim 2, the specific surface area is 200 m² 2 / g or more 450m 2 Zirconium hydroxide powder characterized by having a content of 1g or less.
Citation Information
Patent Citations
Zirconium oxide hydrate particle, and dispersion and disperse film using the same
JP2009274897A
zirconium hydroxide
JP2009525250A
Zirconium hydrate powder
JP2012504093A
